1998
DOI: 10.1152/ajpgi.1998.274.2.g413
|View full text |Cite
|
Sign up to set email alerts
|

Significant cholinergic role in secretin-stimulated exocrine secretion in isolated rat pancreas

Abstract: Effects of intrapancreatic cholinergic activation by electrical field stimulation (EFS) on secretin-stimulated pancreatic exocrine secretion were investigated in the totally isolated perfused rat pancreas. EFS at 15 V, 2 ms, and 8 Hz for 45 min markedly increased spontaneous pancreatic secretion. This increase was completely inhibited by tetrodotoxin (1 μM) but not by hexamethonium (100 μM). Atropine (2 μM) significantly reduced the EFS-evoked volume flow and amylase output by 52% and 80%, respectively. EFS fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…4). This scenario would explain the long-standing observation in pancreatic physiology-the fact that in the intact pancreas the stimulation of acini potentiates the effect of secretin on the production of the HCO À 3 -rich juice [164,165]. Figure 4 shows the working model for how ATP, and/or hydrolytic products as well as the associated enzymes and receptors, could play a role as auto/paracrine regulators in the pancreas.…”
Section: Integrated Pancreatic Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…4). This scenario would explain the long-standing observation in pancreatic physiology-the fact that in the intact pancreas the stimulation of acini potentiates the effect of secretin on the production of the HCO À 3 -rich juice [164,165]. Figure 4 shows the working model for how ATP, and/or hydrolytic products as well as the associated enzymes and receptors, could play a role as auto/paracrine regulators in the pancreas.…”
Section: Integrated Pancreatic Functionmentioning
confidence: 98%
“…Functionally, several islet hormones affect acinar and ductal secretion [166], e.g. insulin potentiates secretin-stimulated secretion in the rat pancreas [165]. Therefore, it is possible that ATP released from β cells could affect closely apposed ductal epithelium.…”
Section: Integrated Pancreatic Functionmentioning
confidence: 99%
“…EFS on rat pancreas enhanced pancreatic exocrine secretion by activation of the intrapancreatic nervous system [8,9]. Pre-treatment of atropine partly blocked this effect, but pre-treatment of tetrodotoxin, a nerve blocker, perfectly blocked it [10]. These results suggested that the non-cholinergic nerve system exists in the intrapancreatic nerve system, and it could affect the pancreatic exocrine secretion.…”
Section: Introductionmentioning
confidence: 87%
“…The isolated pancreas was prepared according to a method described previously [10]. The rats were anesthetized with a single injection of urethane.…”
Section: Preparation Of the Isolated Perfused Pancreasmentioning
confidence: 99%
“…Even cholinergic stimulation and CCK can evoke HCO 3 2 secretion in some species, and they can potentiate the secretin effect on the volume of secretion (You et al 1983;Holst 1993;Park et al 1998;Chey and Chang 2001), although there are exceptions (Evans et al 1996). Whether human pancreatic juice is also rich in HCO 3 2 under these conditions is not clear.…”
Section: Regulation Of Pancreatic Duct Secretionmentioning
confidence: 99%